Effect of processing on the proximate, mineral, and pasting properties of whole flour made from some new plantain and banana hybrids pulp and peel mixture - Adeniji, T.A.; Tenkouano, A. (2008)
The effect of processing on the proximate and mineral composition, as well as pasting properties of whole flour produced from a selection of new Musa hybrids generated by the International Institute ofTropical Agriculture (IITA) was investigated. Results show that blanching had signiftcant effect (p<0.05) on the prortmatu composition, mineral contents and pasting properties of whole Musa flour. However, there was no significant treatment effect (p>0.05) on the moisture, potassium and zinc content of the flaur. Some of the pasting properties of the flour, including peak viscosity, final viscosigt, setback viscosity and pasting time were not significantly dffirent (p>0.05) across various treahnents used. This finding suggests that traditional method of peeling plantain and banana fingers without blanching could be more beneficial based on the nutri.ent profiles, time and resources required to accomplish the blanching process. Whole plantain and banana flour may constitute an important feeding stuff for livestock, which may eventually provide protein in human diet from consumption of meat and other products from livestock,